Alterações do acoplamento excitação-contração em camundongos com hiperatividade simpática - Humberto Cavalcante Joca (2016)
The sympathetic nervous system is essential for maintenance of cardiac function via activation of post-junctional adrenergic receptors. However, adrenergic receptor activation also has deleterious long-term effects, inducing hypertrophy and contribute to the progressive development of heart failure. This study aims analyze the possible deleterious effects in the excitation-contraction coupling in ventricular cardiomyocytes of mice with sympathetic hyperactivity through the double knock-out adrenoceptor α2A and α2C (DKO). We used male DKO mice in a genetic background C57BL6 / J and wild-type controls (WT) mice aged 3 to 7 months. Cardiomyocytes were isolated enzymatically as described previously, and the record of cellular contractility was performed in edge detection system by a CCD camera, the electrophysiological recordings were performed using the patch-clamp technique and calcium transient and levels of reactive species oxygen and nitric oxide were monitored using confocal and fluorescence microscopy, respectively. At 7 months, when compared to the WT (p <0.05; ANOVA followed by Tukey), cardiomyocytes of DKO animals show various changes in contractility such as a reduction in fractional shortening (DKO: 6.4 ± 0.3% / WT: 9.5 ± 0.8%) and the increase in the time for 50% relaxation (DKO: 49.8 ± 2.0% / WT: 41.2 ± 1.0%). Furthermore, DKO cells has several electrophysiological changes such as prolongation of action potential - AP(50% repolarization - DKO: 14.8 ± 1.3 ms / WT: 7.2 ± 0.7 ms), reduction in the density of the calcium current (DKO: -9.6 ± 0.6 A/F / WT: -14.3 ± 0.6 A/F) and potassium current (DKO: 39.6 ± 3.2 A/F / WT: 55.6 ± 2.9 A/F). Associated with observed reduction in contractility and the calcium currents, the calcium transient from DKO animals was reduced (DKO: 2.7 ± 0.4 F / F0 / WT: 3.2 ± 0.5 F / F0) and with slower decay (50% decay - DKO: 185.5 ± 3.9 ms / WT: 148.9 ± 2.5 ms). There were no changes in resting potential, amplitude of the AP and current density of the inward rectifiers. DKO cardiomyocytes also had higher levels of reactive oxygen species, however without changing the nitric oxide levels. On other hand, DKO cardiomyocyte of 3 months-old mice did not show any change in the parameters of AP and cellular contractility compared to WT myocytes. In conclusion, chronic sympathetic hyperactivity impairs cardiac excitation-contraction coupling, by changing the density of several ionic currents (and thus AP repolarization), which correlates directly with the calcium dynamics and contractile activity. This demonstrates the important role of increased sympathetic activity in the electrophysiological remodeling that occurs in cardiac dysfunction.